Bonding material and method for manufacturing bonded body
By using a bonding material with approximately spherical silver or copper particles of D50 of 0.3–0.5 μm and a low solvent content, and firing under low pressure, the cracking problem caused by high pressure in the prior art is solved, and a joint with fewer pores and high thermal conductivity is achieved.
Patent Information
- Application Number
- CN202480027113.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-04-25
- Filing Date
- 2024-04-19
- Publication Date
- 2025-11-25
AI Technical Summary
Existing technologies using silver or copper particle bonding materials may cause semiconductor chips to crack or substrates to deform under high pressure. Furthermore, the dried material is prone to cracking when the thickness increases, and the high porosity affects thermal conductivity and reliability.
A bonding material containing approximately spherical metal particles (A) and a solvent is used. The metal particles (A) have a D50 of 0.3–0.5 μm and a Dmin greater than 0.08 μm. The solvent content is less than 0.01%. The material is fired under low pressure to form a bonding part with fewer pores.
Even if the dried bonding material is thick, it can suppress cracking, form a joint with high thermal conductivity and reliability, and reduce porosity.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to a joining material and a method for manufacturing a joined body.
[0002] This application claims priority based on Japanese Patent Application No. 2023-071339 filed on April 25, 2023, and the contents thereof are hereby incorporated by reference. BACKGROUND
[0003] Since silver and copper have high thermal conductivity and high melting points, they are expected as raw materials of a joining material that replaces solder when joining electrically conductive members to each other. In particular, silver and copper are expected to be highly useful as mounting materials for power semiconductors having high heat generation density. However, in the case of using a joining material containing silver particles or copper particles, the joining material is generally fired at a temperature below the melting point of these metals to join electrically conductive members to each other (in other words, sintering diffusion joining). Therefore, the joint portion formed by sintering becomes a porous body containing many voids in the inside thereof. However, when the operating temperature of a semiconductor greatly fluctuates, thermal stress is generated in the joint portion, and the voids become a source of concentration thereof, leading to breakage of the joint portion. In addition, the thermal conductivity of the joint portion in which voids exist is reduced. Therefore, it is preferable that the voids generated in the inside of the joint portion be as few as possible.
[0004] On the other hand, in order to form a sintered film in which voids are few and dense, a method of pressing a laminate of an electrically conductive member and a joining material in the stacking direction thereof while heating the joining material is generally employed. As a method of forming such a sintered film, for example, a method of using a joining material containing silver nanoparticles (particle diameter 20 nm), heating a laminate of an electrically conductive member and a joining material at 300°C, and pressing at a pressure of 60 MPa to form a sintered film having a void ratio of about 2.5% is disclosed. Furthermore, a method of using a joining material containing silver nanoparticles (particle diameter 18 nm), silver submicron particles (particle diameter 150 nm), and silver micron particles (particle diameter 5063 nm) to form a sintered film having a void ratio of about 8% is disclosed (above, refer to Non-Patent Literature 1). In this way, a joined body obtained by joining electrically conductive members to each other using a joining material containing silver nanoparticles has the advantages of high thermal shock test resistance and high reliability.
[0005] PRIOR ART DOCUMENTS
[0006] NON-PATENT LITERATURE
[0007] Non-Patent Literature 1: Degradation Mechanism of Pressure-Assisted Sintered Silver by Thermal Shock Test, Energies 2021, 14, 5532 SUMMARY
[0008] PROBLEMS TO BE SOLVED BY THE INVENTION
[0009] However, in the method described in Non-Patent Literature 1, pressurization at such a high pressure as 60 MPa has a risk of causing cracking of the semiconductor chip or deformation of the substrate, and in addition, the press used at the time of pressurization needs to be frequently maintained. In order to avoid these problems, it is required to set the pressure at the time of pressurization to 20 MPa or less, but such a means is not disclosed in Non-Patent Literature 1.
[0010] In addition, in the method described in Non-Patent Literature 1, in the case where the thickness of the joint portion (sintering film) is made thick, particularly in the case where it is set to a thickness of 100 μm or more, when the joint material is dried during the formation of the joint portion, cracking is sometimes likely to occur along with the shrinkage of the dried material.
[0011] The present application has an object to provide a joint material which is a joint material for forming a joint portion that joins electrically conductive members to each other, and which, when a joint portion is formed from the joint material, can suppress cracking even if the thickness of the joint material after drying is thick, and can form a joint portion with few voids even if firing is performed while pressurizing the joint material after drying at a low pressure of 20 MPa or less.
[0012] MEANS FOR SOLVING THE PROBLEMS
[0013] In order to solve the above problems, the present application adopts the following configuration.
[0014] [1] A joint material which is a joint material for joining electrically conductive members to each other, comprising: metal particles including substantially spherical metal particles (A), and a solvent that disperses the metal particles, the particle diameter D50 of the metal particles (A) at 50% by volume as measured by laser diffraction / scattering type particle size distribution measurement being 0.3 to 0.5 μm, and the minimum value Dmin of the particle diameter of the metal particles (A) being greater than 0.08 μm.
[0015] [2] The joint material according to [1], wherein the metal particles have metal particles (B) that are different from the metal particles (A), and the minimum value Dmin of the particle diameter of the metal particles (B) as measured by laser diffraction / scattering type particle size distribution measurement is greater than 0.08 μm.
[0016] [3] The joint material according to [1] or [2], wherein a resin component that is a curable resin, a non-curable resin, or a thermoplastic resin is further included in the solvent, and the content of the resin component in the joint material is less than 0.01 mass% relative to the content of the metal particles.
[0017] [4] According to [1] or [2], wherein the bonding material does not contain a resin component in the solvent as a curable resin, a non-curable resin or a thermoplastic resin.
[0018] [5] The bonding material according to any one of [1] to [4], wherein the particle size D90 of the metal particles (A) at 90% volume basis, as determined by laser diffraction / scattering particle size distribution measurement, is less than 0.8 μm.
[0019] [6] The bonding material according to any one of [1] to [5], wherein the metal particles (A) and the metal particles (B) are both silver particles.
[0020] [7] The bonding material according to any one of [1] to [6], wherein the specific surface area of the metal particles (A) is between 0.95 and 1.5 m². 2 Within the range of / g.
[0021] [8] A method for manufacturing a joint body, which is a method for manufacturing a joint body formed by joining a conductive first component and a conductive second component via a conductive joint portion, comprising: a step of attaching a bonding material as described in any one of [1] to [7] to a first surface of the first component or a second surface of the second component; a step of forming a dried bonding material by drying the attached bonding material; a step of stacking the first component and the second component via the dried bonding material to produce a laminated body; and a step of forming the joint portion from the dried bonding material by firing the dried bonding material in the laminated body at a temperature higher than the temperature at which the bonding material is dried.
[0022] [9] The manufacturing method of the joint according to [8], wherein the thickness of the joint is 100 μm or more.
[0023] The effects of the invention
[0024] According to the present invention, a bonding material is provided for forming a joint that joins conductive components together. When the joint is formed from the bonding material, even if the thickness of the dried bonding material is relatively thick, cracking can be suppressed. Even if the dried bonding material is pressed and fired at a low pressure of less than 20 MPa, a joint with fewer pores can be formed. Attached Figure Description
[0025] [ Figure 1is a cross-sectional view schematically showing one example of a bonded body which is an application object of the manufacturing method according to one embodiment of the present application.
[0026] [ Figure 2A ] is a cross-sectional view for schematically explaining one example of the manufacturing method of a bonded body according to one embodiment of the present application, and is a view for explaining the attaching step.
[0027] [ Figure 2B ] is a view for explaining the drying step after the step of Figure 2A .
[0028] [ Figure 2C ] is a view for explaining the lamination step after the step of Figure 2B .
[0029] [ Figure 2D ] is a view for explaining the firing step after the step of Figure 2C .
[0030] [ Figure 2E ] is a view of the bonded body after the step of Figure 2D .
[0031] [ Figure 3A ] is a cross-sectional view for schematically explaining another example of the manufacturing method of a bonded body according to one embodiment of the present application, and is a view for explaining the attaching step.
[0032] [ Figure 3B ] is a view for explaining the drying step after the step of Figure 3A .
[0033] [ Figure 3C ] is a view for explaining the lamination step after the step of Figure 3B .
[0034] [ Figure 3D ] is a view for explaining the firing step after the step of Figure 3C .
[0035] [ Figure 3E ] is a view of the bonded body after the step of Figure 3D .
[0036] [ Figure 4 ] is image data of the metal particles (A)-1 used in Example 1, acquired by SEM.
[0037] [ Figure 5 ] is image data of the metal particles (A)-1 used in Example 2, acquired by SEM.
[0038] [ Figure 6is image data obtained by SEM of the metal particles (B)-1 used in Comparative Example 1.
[0039] [ Figure 7 ] is image data obtained by SEM of the metal particles (B)-2 used in Comparative Example 2.
[0040] [ Figure 8 ] is image data obtained by SEM of the metal particles (B)-3 used in Comparative Example 3. DETAILED DESCRIPTION
[0041] ■Bonding material
[0042] One embodiment of the present application relates to a bonding material provided with: metal particles including substantially spherical metal particles (A), and a solvent in which the metal particles are dispersed, the bonding material having a particle diameter D50 of the metal particles (A) at 50% by volume as measured by laser diffraction / scattering particle size distribution measurement of 0.3 to 0.5 μm, and a minimum value Dmin of the particle diameter of the metal particles (A) of more than 0.08 μm.
[0043] According to this configuration, when a bonding portion is formed from the bonding material, even if the thickness of the dried product of the bonding material, that is, the bonding material after drying, is thick, the bonding material after drying can be inhibited from being broken. In addition, in a laminate obtained by stacking members each having conductivity via the bonding material after drying, even if firing is performed while the bonding material after drying is pressurized at a low pressure of 20 MPa or less, a bonding portion having few voids can be formed.
[0044] Hereinafter, the bonding material in the present embodiment will be described. Note that in the bonding material, the total content of one or two or more of the following-described contained components of the bonding material is not more than 100% by mass with respect to the total mass of the bonding material.
[0045] Metal particles
[0046] In the present embodiment, the bonding material contains at least the metal particles (A). Details will be described later, but the metal particles can further include the metal particles (B).
[0047] The metal particles (A) have a substantially spherical shape.
[0048] In the present specification, the substantially spherical shape means a shape that is spherical or can be regarded as spherical regardless of the case of the metal particles (A), and more specifically, means a shape of a particle in which an aspect ratio obtained by dividing [a long diameter of the particle] by [a short diameter of the particle] is 2 or less. The aspect ratio is preferably 1.6 or less, and more preferably 1.3 or less. The surface of the substantially spherical particle can be constituted only by a curved surface, can have a flat surface, or can have a corner portion in which two flat surfaces are connected to each other at a prescribed angle. The surface of the substantially spherical particle can be smooth, or can have a concave-convex portion.
[0049] As the metal particles (A), all of the metal particles in which the shape is spherical or substantially spherical among commercially available products can be used as long as the particle diameter condition described above is satisfied.
[0050] The kind of metal of the metal particles (A) is preferably a metal that is high in thermal conductivity and high in melting point.
[0051] For example, the thermal conductivity (for example, the thermal conductivity of a bulk) of the kind of metal of the metal particles (A) is preferably 350 W / mK or more, and can be 350 to 450 W / mK. Thereby, for example, even in a case where the heat generation temperature of a semiconductor or the like contacted by the joining material becomes high (for example, 150°C or more), heat can be rapidly dissipated.
[0052] For example, the melting point of the kind of metal of the metal particles (A) is preferably 900°C or more, and can be 900 to 1100°C.
[0053] The kind of metal of the metal particles (A) contained in the joining material can be only one kind, or can be two or more kinds, and in a case where it is two or more kinds, the combination and the ratio thereof can be arbitrarily selected.
[0054] Among them, the kind of metal of the metal particles (A) is preferably silver or copper, and more preferably silver. That is, the metal particles (A) are preferably silver particles or copper particles, and more preferably silver particles. Note that the kind of metal of the metal particles (A) is not limited to pure silver or pure copper, and can be a silver alloy or a copper alloy.
[0055] Among the metal particles (A), as the silver particles, for example, silver particles obtained by a reduction method and silver particles obtained by an atomization method can be listed.
[0056] The silver particles can be surface-treated products in which the surface is subjected to chemical treatment (treatment with a chemical substance), or can be surface-untreated products in which the surface is not subjected to chemical treatment.
[0057] Generally, the silver particles obtained by the reduction method are surface-treated products, and the silver particles obtained by the atomization method are surface-untreated products.
[0058] <Particle diameter distribution of metal particles>
[0059] In the present embodiment, the particle distribution of the metal particles is measured by laser diffraction / scattering particle size distribution measurement.
[0060] Hereinafter, the minimum value of the particle size of the metal particles measured by laser diffraction / scattering particle size distribution measurement is referred to as "Dmin", the particle size of the metal particles at which 10% is accumulated on a volume basis is referred to as "D10", the particle size of the metal particles at which 50% is accumulated on a volume basis is referred to as "D50", the particle size of the metal particles at which 90% is accumulated on a volume basis is referred to as "D90", and the maximum value of the particle size of the metal particles is referred to as "Dmax".
[0061] The D50 of the metal particles (A) is 0.3 to 0.5 μm, and for example, can be any one of 0.3 to 0.4 μm, 0.45 to 0.5 μm, and 0.35 to 0.45 μm. By the D50 being the lower limit value or more, even if the thickness of the dried bonding material is thick, the effect of suppressing the breakage of the dried bonding material can be improved. By the D50 being the upper limit value or less, even if the sintering is performed while the dried bonding material is pressed with a low pressure, the effect of forming a bonding portion with few voids can be improved.
[0062] The Dmin of the metal particles (A) is more than 0.08 μm, and the bonding material can not contain particles having a particle size of 0.08 μm or less as the metal particles (A). In other words, for example, when the particle size on a volume basis of the metal particles (A) is measured by laser diffraction / scattering particle size distribution measurement, particles having a particle size of 0.08 μm or less are not observed. By using such metal particles (A), even if the thickness of the dried bonding material is thick, the breakage of the dried bonding material can be suppressed.
[0063] The Dmin of the metal particles (A) is more than 0.08 μm, and is preferably 0.09 μm or more, and for example, can be 0.12 μm or more, or 0.15 μm or more. By the Dmin being in such a range, even if the thickness of the dried bonding material is thick, the effect of suppressing the breakage of the dried bonding material can be further improved.
[0064] On the other hand, the Dmin is preferably 0.21 μm or less. Such metal particles (A) are more easily prepared as particles, and can be easily obtained. This is because, for example, the manufacturing difficulty of particles in which the D50 is in the range of 0.3 to 0.5 μm and the Dmin is more than 0.21 μm (i.e., particles with a narrow particle size distribution) sometimes becomes high.
[0065] In one embodiment, Dmin may, for example, be any one of greater than 0.08 μm and 0.21 μm or less, 0.09 to 0.21 μm, 0.12 to 0.21 μm, and 0.15 to 0.21 μm. However, these are one example of Dmin.
[0066] D90 of the metal particles (A) is not particularly limited, and is preferably less than 0.8 μm, more preferably 0.78 μm or less, and may, for example, be 0.72 μm or less or 0.65 μm or less. By having D90 in such a range, the effect of forming a joint portion with few voids can be further improved even if the dried joint material is subjected to pressing at a low pressure while being fired.
[0067] On the other hand, D90 is preferably 0.45 μm or more. Such metal particles (A) are easier to produce particles, and can be easily obtained. This is because, for example, the manufacturing difficulty of particles in which D50 is in the range of 0.3 to 0.5 μm and D90 is less than 0.45 μm (i.e., particles with a narrow particle size distribution) sometimes becomes high.
[0068] In one embodiment, D90 may, for example, be any one of 0.45 μm or more and less than 0.8 μm, 0.45 to 0.78 μm, 0.45 to 0.72 μm, and 0.45 to 0.65 μm or less. However, these are one example of D90.
[0069] D10 of the metal particles (A) is not particularly limited, and is preferably 0.18 μm or more, and may, for example, be 0.24 μm or more or 0.3 μm or more. By having D10 in such a range, the effect of suppressing the breakage of the dried joint material can be further improved even if the thickness of the dried joint material is thick.
[0070] On the other hand, D10 is preferably 0.34 μm or less. Such metal particles (A) are easier to produce particles, and can be easily obtained. This is because, as described above, the manufacturing difficulty of particles with a narrow particle size distribution sometimes becomes high.
[0071] In one embodiment, D10 may, for example, be any one of 0.18 to 0.34 μm, 0.24 to 0.34 μm, and 0.3 to 0.34 μm. However, these are one example of D10.
[0072] The Dmax of the metal particles (A) is preferably 2 μm or less. In other words, for example, when the particle diameter of the metal particles (A) is measured by a laser diffraction / scattering type particle diameter distribution measurement, it is preferable that no particles having a particle diameter of more than 2 μm are observed. Further, the Dmax may, for example, be 1.85 μm or less or 1.7 μm or less. By having the Dmax within such a range, even if the joining material after drying is subjected to pressing at a low pressure and then fired, the effect of forming a joint having few voids can be further improved.
[0073] On the other hand, the Dmax is preferably 1.5 μm or more. Such metal particles (A) are more easily produced and can be easily obtained. This is because, as described above, the degree of difficulty in producing particles having a narrow particle size distribution sometimes becomes high.
[0074] In one embodiment, the Dmax may, for example, be any one of 1.5 to 2 μm, 1.5 to 1.85 μm, and 1.5 to 1.7 μm. However, these are one example of the Dmax.
[0075] The specific surface area of the metal particles (A) is not particularly limited and is preferably 0.8 to 1.7 m 2 / g, may, for example, be any one of 0.8 to 1.3 m 2 / g, 1.1 to 1.7 m 2 / g, and 1.1 to 1.3 m 2 / g. By having the specific surface area of the metal particles (A) within such a range, the joining material has a more suitable adhesiveness to apply a printing, coating, or the like attachment method.
[0076] The specific surface area of the particles is not limited to the metal particles (A) and may, for example, be measured by a known method such as a transmission method, a gas adsorption method using gas molecules such as nitrogen, or the like.
[0077] In the joining material, the proportion of the content of the metal particles (A) with respect to the total mass of the joining material ([content (mass parts) of the metal particles (A) of the joining material] / [total mass (mass parts) of the joining material] x 100) is preferably 60 to 93 mass%, may, for example, be any one of 70 to 93 mass% and 80 to 93 mass%. By having the proportion be the lower limit value or more, the joint can be more effectively formed. By having the proportion be the upper limit value or less, the flowability of the joining material becomes higher, and thus the handling property of the joining material becomes higher.
[0078] Solvent
[0079] The joining material has flowability by containing a solvent and has a good handling property.
[0080] The bonding material is typically paste-like or liquid-like.
[0081] In the present specification, unless otherwise specified, "solvent" is a concept including both a component that is liquid at ordinary temperature for dissolving a solute and a component that functions as a dispersion medium for dispersing a dispersed phase, which is liquid at ordinary temperature.
[0082] In the present specification, "ordinary temperature" means a temperature without special cooling or heating, that is, a usual temperature, and for example, a temperature of 15 to 25°C can be mentioned.
[0083] The solvent is not particularly limited as long as it can be removed (vaporized) under heating conditions, and is preferably a solvent that is not reactive with components other than the solvent in the bonding material, such as the metal particles (A).
[0084] As the solvent, for example, aromatic hydrocarbons such as toluene, o-xylene, m-xylene, p-xylene, and the like; aliphatic hydrocarbons such as pentane, hexane, cyclohexane, heptane, octane, cyclooctane, nonane, decane, undecane, dodecane, tridecane, tetradecane, pentadecane, and the like; halogenated hydrocarbons such as dichloromethane, chloroform, and the like; alcohols such as hexanol (for example, 1-hexanol, and the like), heptanol (for example, 1-heptanol, and the like), octanol (for example, 1-octanol, and the like), nonanol (for example, 1-nonanol, and the like), decanol (for example, 1-decanol, and the like), benzyl alcohol, cyclohexanol, terpineol (alias: terpinen-4-ol), and the like; esters such as ethyl acetate, monomethyl glutarate, dimethyl glutarate, and the like; ethers such as diethyl ether, tetrahydrofuran (THF), 1,2-dimethoxyethane (dimethyl cellosolve), and the like; glycol ethers (compounds having both a hydroxyl group and an ether bond in one molecule) such as propylene glycol monomethyl ether (alias: 1-methoxy-2-propanol), 3-methoxy-3-methyl-1-butanol, butyl carbitol (alias: diethylene glycol monobutyl ether), and the like; ketones such as acetone, methyl ethyl ketone (MEK), cyclohexanone, 2-octanone, diisobutyl ketone (alias: 2,6-dimethyl-4-heptanone), and the like; hydroxy ketones such as diaceton alcohol (alias: 4-hydroxy-4-methyl-2-pentanone), and the like; enones such as isophorone (alias: 3,5,5-trimethylcyclohex-2-en-1-one), and the like; nitriles such as acetonitrile, and the like; amides such as N,N-dimethylformamide (DMF), N,N-dimethylacetamide, and the like; glycol esters (compounds having both a hydroxyl group and an ester bond in one molecule) such as Texanol (2,2,4-trimethyl-1,3-pentanediol monoisobutyrate), and the like can be mentioned.
[0085] The solvent contained in the bonding material can be only one, or two or more, and in the case of two or more, their combination and ratio can be arbitrarily selected.
[0086] The content of the solvent in the joining material is preferably 7 to 40 mass% with respect to the total mass of the joining material ([content of the solvent in the joining material (mass part)] / [total mass of the joining material (mass part)] x 100), and can be any one of 7 to 30 mass% and 7 to 20 mass%, for example. By the proportion being the lower limit value or more, the flowability of the joining material becomes higher, and thus the handling property of the joining material becomes higher. By the proportion being the upper limit value or less, the content of the metal particles (A) of the joining material can be further increased, and the joining portion can be more effectively formed.
[0087] Other Components
[0088] The joining material can also contain other components other than any of the metal particles (A) and the solvent, or can not contain them, within a range not impairing the effects of the present application.
[0089] The other components are not particularly limited as long as the effects of the present application are not impaired, and can be arbitrarily selected according to the purpose.
[0090] The other components contained in the joining material can be only one, or can be two or more, and in the case of two or more, their combination and ratio can be arbitrarily selected.
[0091] As the other components contained in the joining material, for example, metal particles (B) other than the metal particles (A), and a resin component can be cited. That is, the joining material can also contain any one or both of the metal particles (B) and the resin component.
[0092] Metal Particles (B)
[0093] The metal particles (B) are metal particles different from the metal particles (A). In the present embodiment, the metal particles (A) and the metal particles (B) are different metal particles means that, for example, the metal species of the particles, the particle size distribution, or the shape of the two kinds of metal particles are different from each other.
[0094] For example, in the case where the metal species of the metal particles (A) is silver, the metal species of the metal particles (B) can be a metal species other than silver (for example, copper). In the case where the shape of the metal particles (A) is a substantially spherical shape, the shape of the metal particles (B) can be a shape other than a substantially spherical shape (for example, a plate shape).
[0095] The particle size distributions of the two kinds of metal particles are different from each other, including cases where D50 is different from each other and cases where the width of the particle size distribution is different from each other. In the case where D50 is different from each other, in the particle size distribution of the mixture in which the two kinds of particles are mixed, the peak portion of the particle size becomes two. In addition, even in the case where D50 of the two kinds of particles is identical, the case where the width of the particle size distribution of the two kinds of metal particles is different from each other is included in the "case where the particle size distribution of the metal particle (A) and the metal particle (B) is different from each other". The case where the width of the particle size distribution of the two kinds of metal particles is different from each other means, for example, the case where at least one of Dmin, D10, D90, or Dmax is different from each other. That is, it means the case where the width of the particle size distribution when the two kinds of particles are mixed is different from the width of the lower side of only one particle size distribution.
[0096] The Dmin of the metal particle (B) is greater than 0.08 μm, and the bonding material can not contain a particle having a particle size of 0.08 μm or less as the metal particle (B). In other words, for example, when the particle size of the metal particle (B) is measured by laser diffraction / scattering particle size distribution measurement on a volume basis, a particle having a particle size of 0.08 μm or less is not observed.
[0097] The metal particle (B) is not particularly limited as long as the above conditions are satisfied.
[0098] As the metal kind of the metal particle (B), the same metal kind as the metal kind of the metal particle (A) can be listed.
[0099] As the metal particle (B), for example, a metal particle having a shape other than a substantially spherical shape, a substantially spherical metal particle having a D50 of less than 0.3 μm, a substantially spherical metal particle having a D50 of greater than 0.5 μm, and the like can be listed.
[0100] As the shape other than a substantially spherical shape of the metal particle (B), as a representative shape, a plate shape can be listed.
[0101] In the present specification, the "plate shape" of the metal particle means a shape having two principal faces, and the shape of the principal face means a substantially polygonal shape such as a substantially triangular shape (a triangle or a shape that can be regarded as a triangle), a substantially pentagonal shape (a pentagon or a shape that can be regarded as a pentagon), or a substantially hexagonal shape (a hexagon or a shape that can be regarded as a hexagon); or an indefinite shape that can be regarded as a shape in which a part of the side or the angle of the substantially polygonal shape is missing.
[0102] The thickness of the plate (that is, the width between the two principal faces, the thickness of the plate in the direction perpendicular to the principal face) is 40 nm or less, and the maximum length of the two principal faces (in other words, the particle size) is 10 to 1000 nm.
[0103] The aspect ratio ([= the maximum length (particle diameter) of the main surface] / [the width between the main surfaces]) of the plate-like metal particles is 3 or more.
[0104] The metal species of the metal particles (B) contained in the joining material can be only one, or two or more, and in the case of two or more, their combination and ratio can be arbitrarily selected.
[0105] The metal species of the metal particles (B) is preferably silver or copper, and more preferably silver. Note that the metal species of the metal particles (B) is not limited to pure silver or pure copper, and can be a silver alloy or a copper alloy.
[0106] Further, both the metal particles (A) and the metal particles (B) contained in the joining material are preferably silver particles.
[0107] In the joining material, the proportion of the content of the metal particles (B) with respect to the total mass of the joining material ([the content (mass parts) of the metal particles (B) of the joining material] / [the total mass (mass parts) of the joining material] x 100) is preferably 1 mass% or less, and for example, can be any one of 0.5 mass% or less, 0.3 mass% or less, and 0.1 mass% or less. By the proportion being the upper limit value or less, the effect obtained by using the metal particles (A) is further improved.
[0108] For the joining material, when the particle diameter of the metal particles on a volume basis is measured by laser diffraction / scattering particle diameter distribution measurement, in the case where a plurality of peaks of particle size distribution is observed, the presence of the metal particles (B) can be confirmed. In the case where the difference between the D50 of the metal particles (B) and the D50 of the metal particles (A) is large, a plurality of peaks can be easily confirmed.
[0109] In the case where the joining material is observed with SEM or the like, in the case where metal particles having a shape other than substantially spherical, such as a plate shape, are observed, the presence of the metal particles (B) can be confirmed.
[0110] <Resin component>
[0111] The resin component can be arbitrarily selected according to the purpose, and is not particularly limited.
[0112] The resin component can be, for example, any one of a curable resin and a non-curable resin, or a thermoplastic resin. The resin component can be dissolved in a solvent or dispersed in a solvent. The resin component can be an adhesive that contributes to the adhesion of metal particles to each other, or the adhesion of the joining material to an adherend, or can be a spacer particle that becomes a spacer between metal particles by being dispersed in a solvent.
[0113] Note that the resin provided on the surface of the metal particles for the purpose of chemical treatment of the surface of the metal particles is not included in the resin component of the present embodiment.
[0114] Note that in the joining material of the present embodiment, it is not necessary to contain a resin component (e.g., a binder or a spacer particle). The less the content of the resin component, the better, and in the joining material, the proportion of the content of the resin component with respect to the total content of the metal particles ([content of the resin component of the joining material (mass parts)] / [total content of the metal particles of the joining material (mass parts)] x 100) is preferably less than 0.01 mass%, and can be 0.005 mass% or less. In the case where the resin component is contained in an amount of less than 0.01 mass%, it is sometimes possible to reduce the porosity of the joining material or suppress the generation of cracks by the resin component. However, when the resin component remains in the joining material after firing, the porosity sometimes becomes high due to the remaining resin component. Therefore, it is preferable that the proportion of the content of the resin component in the joining material be less than 0.01 mass% or that the joining material not contain the resin component.
[0115] Thus, it can be considered that the proportion of the content of the resin component is preferably 0 mass% or more and less than 0.01 mass%.
[0116] By the proportion being less than 0.01 mass% or the joining material not containing the resin component, even if the thickness of the joining material after drying is thick, the effect of suppressing the breaking of the joining material after drying can be further improved, and even if the joining material after drying is fired while being pressed at a low pressure, the effect of forming a joining portion with few pores can be further improved.
[0117] The resin component contained in the joining material can be only one kind, or can be two or more kinds, and in the case where there are two or more kinds, their combination and ratio can be arbitrarily selected.
[0118] In the joining material, in the case where the metal particles include metal particles (A) and metal particles (B), the proportion of the content of the resin component with respect to the total content of the metal particles (A) and the metal particles (B) is [content of the resin component of the joining material (mass parts)] / [total content of the metal particles (A) and the metal particles (B) of the joining material (mass parts)] x 100. In this case as well, the proportion of the content of the resin component is less than 0.01 mass%, and can be 0.005 mass% or less, for example.
[0119] Here, in the case where the joining material does not contain the metal particles (B), the content of the metal particles (B) of the joining material is 0 mass parts. Similarly, in the case where the joining material does not contain the resin component, the content of the resin component of the joining material is 0 mass parts.
[0120] The joining material can contain a component (X) that is not either of the metal particles (B) and the resin component as the other component. In this case, in the joining material, the proportion of the content of the component (X) with respect to the total mass of the joining material ([content (mass parts) of the component (X)] / [total mass (mass parts) of the joining material] x 100) is preferably 5% by mass or less, for example, can be either of 3% by mass or less and 1% by mass or less. By the proportion being the upper limit value or less, even if the thickness of the joining material after drying is thick, the effect of suppressing the joining material after drying from breaking can be further improved, and even if firing is performed while the joining material after drying is pressed at a low pressure, the effect of forming a joining portion with few voids can be further improved.
[0121] On the other hand, the proportion of the content of the component (X) is 0% by mass or more.
[0122] In the joining material, the proportion of the total content of the metal particles (A) and the solvent with respect to the total mass of the joining material ([total content (mass parts) of the metal particles (A) and the solvent of the joining material] / [total mass (mass parts) of the joining material] x 100) is preferably 95% by mass or more, for example, can be either of 97% by mass or more and 99% by mass or more. By the proportion being the lower limit value or more, even if the thickness of the joining material after drying is thick, the effect of suppressing the joining material after drying from breaking can be further improved, and even if firing is performed while the joining material after drying is pressed at a low pressure, the effect of forming a joining portion with few voids can be further improved.
[0123] On the other hand, the proportion of the total content of the metal particles (A) and the solvent with respect to the total mass of the joining material is 100% by mass or less.
[0124] As described above, the joining material according to the present embodiment includes metal particles including substantially spherical metal particles (A), and a solvent that disperses the metal particles, the particle diameter D50 of the metal particles (A) at 50% by volume as measured by laser diffraction / scattering particle diameter distribution measurement is 0.3 to 0.5 μm, and the minimum value Dmin of the particle diameter of the metal particles (A) is greater than 0.08 μm.
[0125] In such a configuration, by D50 being in the range of 0.3 to 0.5 μm, even if the thickness of the joining material after drying is thick, the joining material after drying can be suppressed from breaking, and even if firing is performed while the joining material after drying is pressed at a low pressure of 20 MPa or less, a joining portion with few voids can be formed.
[0126] Further, by making Dmin greater than 0.08 μm, even if the thickness of the joint material after drying is thick, it is possible to suppress the joint material after drying from breaking.
[0127] Thus, in the laminate in which the joint material of the present embodiment is sandwiched by the electrically conductive member, even if firing is performed while being pressed at a low pressure of 20 MPa or less, it is possible to form a joint having few voids.
[0128] Note that the metal particles can also have metal particles (B) that are different from the metal particles (A). The minimum value Dmin of the particle diameter of the metal particles (B) measured by laser diffraction / scattering particle diameter distribution measurement is greater than 0.08 μm.
[0129] Further, the solvent also has a resin component that is a curable resin, a non-curable resin, or a thermoplastic resin, and the content of the resin component in the joint material is less than 0.01 mass% relative to the content of the metal particles. Alternatively, the joint material does not have a resin component that is a curable resin, a non-curable resin, or a thermoplastic resin in the solvent.
[0130] Thus, it is possible to reduce the void ratio of the joint material or suppress the generation of cracks.
[0131] Method for manufacturing a joint material
[0132] The joint material of the present embodiment is obtained by compounding the metal particles (A), the solvent, and the other components as necessary.
[0133] After the components are compounded, the obtained substance can be directly used as the joint material, or a substance obtained by further performing a publicly known post-treatment operation or a refining operation as necessary can be used as the joint material.
[0134] The order of compounding the components is not particularly limited.
[0135] The mixing method of the compound is not particularly limited, and can be appropriately selected from publicly known methods such as a method in which a stirrer or a stirring wing or the like is rotated to mix, a method in which a blender, a three-roll mill, a kneader, or a bead mill or the like is used to mix, a method in which ultrasonic waves are applied to mix, and the like.
[0136] The temperature at the time of compounding the components is not particularly limited as long as the compounded components do not deteriorate, and is preferably 0 to 40°C.
[0137] The compounding time of the components is not particularly limited as long as the compounded components do not deteriorate, and is preferably 10 minutes to 12 hours.
[0138] Method for manufacturing a joint body
[0139] One embodiment of the present application relates to a method for manufacturing a bonded body by bonding a first electrically conductive member (hereinafter, sometimes referred to simply as "first member") and a second electrically conductive member (hereinafter, sometimes referred to simply as "second member") via an electrically conductive bonding portion (hereinafter, sometimes referred to simply as "bonding portion"), and includes:
[0140] a step (hereinafter, sometimes referred to as "adhesion step") of adhering the bonding material to the first surface of the first member or the second surface of the second member;
[0141] a step (hereinafter, sometimes referred to as "drying step") of forming a dried bonding material by drying the adhered bonding material;
[0142] a step (hereinafter, sometimes referred to as "stacking step") of stacking the first member and the second member via the dried bonding material to produce a stacked body; and
[0143] a step (hereinafter, sometimes referred to as "firing step") of forming the bonding portion from the dried bonding material by firing the dried bonding material in the stacked body at a temperature higher than the temperature at which the bonding material is dried.
[0144] The electrically conductive member such as the first member and the second member is not particularly limited as long as it has electrical conductivity. As the electrically conductive member, for example, a metal member can be cited. The metal member can be, for example, a metal layer provided on the surface of a semiconductor chip such as a silicon chip or a semiconductor element by a sputtering method or a plating method, or a metal layer such as an electrode provided on a resin substrate or a ceramic substrate.
[0145] The bonding portion is formed using the bonding material according to one embodiment described above, and is a metal sintered body.
[0146] For example, in the case where the bonding material contains silver particles as the metal particles (A), the metal sintered body is a silver sintered body, and in the case where the bonding material contains copper particles as the metal particles (A), the metal sintered body is a copper sintered body.
[0147] The bonding portion has electrical conductivity and thermal conductivity, and is useful instead of solder.
[0148] In the manufacturing method, any of the steps can be performed in the atmosphere.
[0149] In a case where the constituent material of either or both of the first member and the second member as the joining object is a metal (for example, copper or the like) that is easily oxidized, in the manufacturing method, any process can be performed under an inert gas atmosphere. As the inert gas, for example, nitrogen gas, helium gas, or the like can be listed.
[0150] Hereinafter, the manufacturing method of the joined body of the present embodiment will be described with reference to the drawings.
[0151] First, the joined body that is the application object of the manufacturing method of the present embodiment will be described.
[0152] Joined Body
[0153] Figure 1 is a cross-sectional view that schematically shows one example of the joined body.
[0154] The joined body 1 shown here is configured by joining the electrically conductive first member 11 and the electrically conductive second member 12 via the electrically conductive joining portion 13.
[0155] The first surface 11a of the first member 11 is in contact with the joining portion 13.
[0156] The second surface 12a of the second member 12 is in contact with the joining portion 13.
[0157] The joined body 1 is configured by stacking the first member 11, the joining portion 13, and the second member 12 in the thickness direction of them in this order. Hereinafter, the stacking direction of the first member 11, the joining portion 13, and the second member 12 will be referred to as the thickness direction.
[0158] The area of the first surface 11a of the first member 11 is preferably equal to or greater than the area of the second surface 12a of the second member 12.
[0159] The first member 11 is in a sheet shape, a plate shape, or a block shape.
[0160] The first member 11 is preferably configured to contain a metal, and is more preferably made of a metal.
[0161] As the metal that configures the first member 11, for example, silver, copper, aluminum, gold, nickel, or the like can be listed.
[0162] The first member 11 can be configured by one layer (single layer), or can be configured by a plurality of layers of two or more layers. In a case where the first member 11 is configured by a plurality of layers, these plurality of layers can be the same as each other, or can be different from each other, and the combination of these plurality of layers is not particularly limited.
[0163] Note that in the present specification, in the case where the first member is not limited to one member, "a plurality of layers can be the same as each other or different from each other" means "all of the layers can be the same, all of the layers can be different, only a part of the layers can be the same", and in addition, "a plurality of layers are different from each other" means "at least one of the constituent material and the thickness of each layer is different from each other".
[0164] In the case where the first member 11 is composed of a plurality of layers, for example, one layer or two or more layers on the side of the bonding portion 13 in the first member 11 can be a layer that improves adhesion to the bonding portion 13.
[0165] The thickness of the first member 11 can be arbitrarily set according to the purpose of the bonded body 1, and is not particularly limited.
[0166] The thickness of the first member 11 can be, for example, 10 to 10,000 μm.
[0167] In the case where the first member 11 is composed of a plurality of layers, it is preferable that the total thickness of the layers be the thickness of the above-described first member 11.
[0168] Here, as the first member 11, a member in the shape of a sheet, a plate, or a block is shown, but the first member 11 can also be in other shapes other than these, and the shape of the first member 11 can be arbitrarily selected according to the purpose.
[0169] The second member 12 is in the shape of a sheet, a plate, or a block.
[0170] The second member 12 is preferably composed of a metal, and more preferably is made of a metal, and as the metal that constitutes the second member 12, the same metals as those that constitute the above-described first member 11 can be listed.
[0171] The second member 12 can be composed of one layer (a single layer), or can be composed of a plurality of layers of two or more layers. In the case where the second member 12 is composed of a plurality of layers, the plurality of layers can be the same as each other or different from each other, and the combination of the plurality of layers is not particularly limited.
[0172] In the case where the second member 12 is composed of a plurality of layers, for example, one layer or two or more layers on the side of the bonding portion 13 in the second member 12 can be a layer that improves adhesion to the bonding portion 13.
[0173] The thickness of the second member 12 can be arbitrarily set according to the purpose of the bonded body 1, and is not particularly limited.
[0174] The thickness of the second member 12 is preferably 0.05 to 10,000 μm, and can be, for example, 0.05 to 500 μm, or can be greater than 500 μm and 10,000 μm or less.
[0175] In the case where the second member 12 is composed of a plurality of layers, the total thickness of the layers is preferably the thickness of the second member 12 described above.
[0176] Here, as the second member 12, a member in a sheet shape, a plate shape, or a block shape is shown, but the second member 12 can be in another shape other than these, and the shape of the second member 12 can be arbitrarily selected according to the purpose.
[0177] The joint portion 13 is in a sheet shape, a plate shape, or a block shape.
[0178] The joint portion 13 can be composed of one layer (single layer) or a plurality of layers of two or more layers. In the case where the joint portion 13 is composed of a plurality of layers, the plurality of layers can be the same as or different from each other, and the combination of the plurality of layers is not particularly limited.
[0179] The entire surface of the first member 11 side of the joint portion 13 is preferably in contact with the first surface 11a of the first member 11.
[0180] The thickness of the joint portion 13 can be, for example, 10 μm or more and less than 100 μm, but is preferably 100 μm or more, for example, any one of 200 μm or more and 300 μm or more. In the case where the thickness of the joint portion 13 is as thick as 100 μm or more, the thickness of the dried joint material also needs to be 100 μm or more, but in this way, in making the thickness of the dried joint material thick, the effect of the present application that the dried joint material can be inhibited from being broken is more remarkably obtained by using the joint material of the present embodiment.
[0181] On the other hand, from the viewpoint of more easily forming the joint portion 13, the thickness of the joint portion 13 is preferably 400 μm or less.
[0182] Here, as the joint portion 13, a joint portion in a sheet shape, a plate shape, or a block shape is shown, but the joint portion 13 can be in another shape other than these, and the shape of the joint portion 13 can be arbitrarily selected according to the purpose.
[0183] Among the surfaces of the joint portion 13, the area of the contact region with the first member 11 (more specifically, the first surface 11a), and the area of the contact region with the second member 12 (more specifically, the second surface 12a) can be the same as or different from each other. The area of the contact region is preferably any one of 9 to 2500 mm 2 , more preferably 9 to 1225 mm 2 , for example, 9 to 576 mm 2 , and 9 to 144 mm 2 , and can also be 225 to 1225 mm 2 , and 625 to 1225 mm 2any one of the above, and can also be 225 to 576 mm 2 However, these are examples of the area of the contact region. When the area of the contact region is within the above range, the joining strength and heat dissipation between the members 11, 12 and the joining portion 13 are improved.
[0184] The area of the second face 12a of the second member 12 with respect to the area of the face of the joining portion 13 on the second member 12 side is preferably 50 to 150%.
[0185] The area of the contact region of the second face 12a of the second member 12 with respect to the entire area of the second face 12a is preferably 50 to 100%.
[0186] In the joining portion 13, the entire face on the first member 11 side is preferably in contact with the first member 11.
[0187] In the joining body 1, one first member 11 and one second member 12 are joined by one joining portion 13, but the joining method is not limited thereto.
[0188] In the joining body, for example, one first member and two or more second members can be joined by one joining portion. In this case, the two or more second members can all be the same, all different, or only a part different.
[0189] In the joining body, for example, one first member and two or more second members can be joined by two or more joining portions. In this case, the number of second members and the number of joining portions can be the same or different. In addition, the two or more second members can all be the same, all different, or only a part different.
[0190] The number of first members and the number of second members exemplified here can also be reversed.
[0191] The joining body that is the application object of the manufacturing method of the present embodiment is not limited to Figure 1 The joining body shown, for example, can be changed, deleted, or a part of the configuration added within the scope of the gist of the present application. Figure 1 The joining body 1 shown can be changed, deleted, or a part of the configuration added.
[0192] "Porosity"
[0193] The porosity is determined by forming a cross section of the joint portion and observing the cross section using a scanning electron microscope (SEM). Note that the joint portion 13 observed is a portion obtained by firing while sandwiching the dried joint material between the first surface 11a and the second surface 12a. That is, the porosity in the joint portion 13 obtained by firing while pressing the first member 11 and the second member 12 with a prescribed pressure is measured.
[0194] Here, in the cross section, the ratio of the area of the portion corresponding to the pores to the area of the cross section ([area of the portion corresponding to the pores in the cross section] / [area of the cross section] x 100) is taken as the "porosity". For example, the ratio of the area of the portion corresponding to the pores in the region surrounded by a prescribed contour line in the cross section of the joint portion 13 to the total area of the region surrounded by the contour line ([area of the portion corresponding to the pores in the region surrounded by the contour line] / [area of the region surrounded by the contour line] x 100) can also be taken as the "porosity".
[0195] The porosity is preferably 5% or less. By using the joint material of the present embodiment, even if firing is performed while pressing the dried joint material with a low pressure of 20 MPa or less, a joint portion with few pores (low porosity) can be formed.
[0196] Note that, as is clear from the description of the method of calculating the porosity, the "area of the cross section" in the calculation formula of the porosity includes not only the area of the portion of the metal sintered body itself but also the area of the portion corresponding to the pores.
[0197] When calculating the porosity of the joint portion, as described later in the examples, in the image data of the cross section obtained using the SEM, 2-value processing is performed using image processing software, the pores are determined, and the porosity is calculated, whereby the porosity can be calculated with higher precision.
[0198] When calculating the porosity of the joint portion, in the case where the portions of the pores do not deviate in the cross section, for example, the porosities can be calculated from the areas surrounded by prescribed contour lines in the image data of the SEM at representative several places (for example, 2 to 3 places) in the cross section, respectively, and the average value thereof can be adopted as the porosity of the joint portion.
[0199] Next, the manufacturing method of the present embodiment will be described with reference to the case where the joint body shown in FIG. 1 is manufactured. Figure 1 The joint body shown in FIG. 1 is manufactured by the following manufacturing method.
[0200] ◎ Manufacturing Method (1)
[0201] Figures 2A-2Eis a cross-sectional view for schematically illustrating one example of a manufacturing method of the joint body of the present embodiment (hereinafter, sometimes referred to as "manufacturing method (1)").
[0202] Note that, in each drawing, the same symbol is attached to the same constituent element as that shown in the explained drawing, and detailed explanation thereof is omitted.
[0203]
[0204] In the attaching step of the manufacturing method (1), as shown in Figure 2A the joining material 130 is attached to the first surface 11a of the first member 11.
[0205] As the method of attaching the joining material 130 to the first member 11, for example, a known method such as a printing method, a coating method, or the like can be listed.
[0206] As the printing method, for example, a screen printing method, a flexographic printing method, an offset printing method, an immersion printing method, an inkjet printing method, a dispenser printing method, an inkjet dispenser printing method, a gravure printing method, a gravure offset printing method, a pad printing method, or the like can be listed.
[0207] As the coating method, for example, a method using various coaters such as a spin coater, an air knife coater, a curtain coater, a die coater, a doctor blade coater, a roll coater, a gate roll coater, a bar coater, a rod coater, a gravure coater, or the like; a method using a wire bar; a method using a coating device such as a slot die; or the like can be listed.
[0208] In attaching the joining material 130 to the first member 11, a mask such as a metal mask can also be used to cause the joining material 130 to be attached only to a target site.
[0209]
[0210] In the drying step after the attaching step of the manufacturing method (1), as shown in Figure 2B the attached joining material 130 is dried to form a dried joining material 130'.
[0211] By the drying step, the solvent in the joining material 130 is volatilized, and thus, in the dried joining material 130', the solvent is not present, or the content of the solvent is greatly reduced compared to the case of the joining material 130.
[0212] The dried joining material 130' is not a metal sintered body, and typically does not have a luster unique to a metal, and from such a characteristic in appearance, it can also be distinguished from a target metal sintered body.
[0213] The drying of the bonding material 130 can be carried out using known methods, preferably by heating under normal pressure.
[0214] The heating temperature (drying temperature) of the bonding material 130 in the drying process can be appropriately adjusted according to the type of solvent, but it is preferably 70°C or higher, for example, either 100°C or higher or 130°C or higher. By heating the material at or above the lower limit, the bonding material 130 can be dried more quickly. In addition, since the solvent can fully evaporate during the drying process, the occurrence of sudden boiling caused by residual solvent in the firing process described later can be prevented, and the formation of voids can be suppressed.
[0215] On the other hand, the heating temperature is preferably below 160°C. By keeping the heating temperature below the upper limit, deterioration of the dried bonding material 130' can be suppressed. For example, if the drying temperature is too high, the metal particles may neck (weld) each other before the firing process, making it difficult to reduce porosity under pressure.
[0216] The heating time (drying time) of the bonding material 130 in the drying process can be appropriately adjusted according to the heating temperature described above, preferably 1 to 40 minutes, for example, any one of 3 to 30 minutes and 5 to 20 minutes. By keeping the heating time within such a range, the target dried bonding material 130' can be formed more effectively.
[0217] The thickness of the dried bonding material 130' can be, for example, 10 μm or more and less than 100 μm, but preferably 100 μm or more, such as either 200 μm or more or 300 μm or more. Conventional bonding materials are prone to cracking when their thickness is relatively large. In contrast, by using the dried bonding material 130', cracking can be suppressed even when its thickness is 100 μm or more.
[0218] On the other hand, from the perspective that it is easier to form the dried bonding material 130', the thickness of the dried bonding material 130' is preferably less than 400 μm.
[0219] Layering Process
[0220] In the lamination process following the drying step in manufacturing method (1), as Figure 2C As shown, the first component 11 and the second component 12 are laminated together by means of the dried bonding material 130' to form a laminate 101. That is, the laminate 101 is formed by sequentially laminating the first component 11, the dried bonding material 130', and the second component 12 in their thickness directions, with the dried bonding material 130' tightly bonded to the first component 11.
[0221] The first member 11 contacts the dried bonding material 130' at the first face 11a.
[0222] The second member 12 contacts the dried bonding material 130' at the second face 12a.
[0223]
[0224] In the firing step after the lamination step of the production method (1), as shown in FIG. 2, the dried bonding material 130' in the laminate 101 is fired at a temperature higher than the temperature at which the bonding material 130 is dried (in this specification, sometimes referred to as "firing temperature"). Figure 2D
[0225] In the case where the drying of the bonding material 130 is performed by heating, the heating temperature of the dried bonding material 130' (the firing temperature) is higher than the heating temperature of the bonding material 130 (the drying temperature).
[0226] The temperature increase rate when the dried bonding material 130' is fired is not particularly limited, and is preferably 30 to 70°C / minute, for example, 40 to 60°C / minute. By the temperature increase rate being in such a range, the metal sintered body (bonding portion 13) of the target characteristics can be more efficiently produced.
[0227] The firing temperature of the dried bonding material 130' (the temperature of the sintered metal particles (A)) is preferably 180°C or higher, for example, any one of 200°C or higher, 220°C or higher, and 240°C or higher. By the firing temperature being the lower limit value or higher, a metal sintered body (bonding portion 13) of higher purity can be obtained.
[0228] On the other hand, from the viewpoint of suppressing excessive heating and obtaining a metal sintered body (bonding portion 13) of good characteristics, the firing temperature of the dried bonding material 130' is preferably 320°C or lower, for example, any one of 300°C or lower and 280°C or lower.
[0229] The firing time of the dried bonding material 130' (the time of sintering the metal particles (A)) is preferably 3 to 120 minutes, for example, any one of 3 to 60 minutes, 50 to 90 minutes, and 80 to 120 minutes. By the firing time (sintering time) being in such a range, the metal sintered body of the target characteristics can be more efficiently produced.
[0230] In the firing step, it is preferable that the firing temperature be set to the above numerical range, and the firing time be set to the numerical range shown here, to perform the firing of the dried bonding material 130'.
[0231] In the firing step, it is preferable to fire the dried bonding material 130' while pressing the laminate 101 in the thickness direction (in this specification, sometimes referred to as "pressing and firing"). In this way, by pressing and firing the dried bonding material 130', a bonding portion with fewer voids can be formed.
[0232] In the case where the laminate 101 is pressed in the thickness direction, as shown in FIG. 6, the pressure applied to the laminate 101 can be either or both of a pressure PI applied from the side of the first member 11 and a pressure P2 applied from the side of the second member 12. Figure 2D
[0233] In this specification, "pressing" means that the pressure applied to an object is increased by an operation of actively applying a force to the object, and for example, in a case where only the object is supported (only a vertical resistance is applied) without the operation of actively applying a force, the object is not pressed. In the case of pressing, for example, the position of a pressing unit changes by itself with acceleration.
[0234] In the pressing and firing, heating for firing the dried bonding material 130' (laminate 101) and pressing of the dried bonding material 130' (laminate 101) can be started at the same time, or heating for firing the dried bonding material 130' can be started first, and then pressing of the dried bonding material 130' can be started, or pressing of the dried bonding material 130' can be started first, and then heating for firing the dried bonding material 130' can be started.
[0235] The pressure applied to the dried bonding material 130' at the time of pressing and firing is preferably 20 MPa or less, and for example, can be 16 MPa or less. Generally, when the pressure at the time of pressing and firing is low, voids in the bonding portion increase, and a dense bonding portion cannot be obtained, but by using the bonding material 130 of the present embodiment, even if the pressure is a low pressure of the upper limit value or less, a dense bonding portion with fewer voids can be obtained. In addition, by the pressure being the upper limit value or less, breakage and deformation of the first member 11 or the second member 12 can be suppressed.
[0236] On the other hand, for example, from the viewpoint that the effect of pressing can be effectively obtained, the pressure at the time of pressing and firing is preferably 1 MPa or more.
[0237] Here, the pressure at which the dried joining material 130' is pressurized (the pressure at the time of pressurized firing) is obtained by dividing the load at the time of pressurizing the laminate 101 by the area of the region of the dried joining material 130' that receives the load. In a case where both the pressure P1 applied from the first member 11 side and the pressure P2 applied from the second member 12 side are applied to the joining material 130', the pressure per unit area at the time of pressurized firing is set to (pressure P1 / area of the first face 11a that receives the pressure P1 + pressure P2 / area of the second face 12a that receives the pressure P2).
[0238] By performing the firing process, as shown in Figure 2E the joining portion 13 is formed from the dried joining material 130', and the target joining body 1 is obtained. The joining portion 13 is a metal sintered body formed from the joining material 130 through the dried joining material 130'.
[0239] By using the joining material 130, the joining portion 13 has few voids. Therefore, even if the temperature of the joining body 1 greatly fluctuates, the concentration of thermal stress in the joining portion 13 can be suppressed, and thus the breakage of the joining portion 13 is suppressed. In addition, since it is formed from metal particles having high thermal conductivity, the joining portion 13 has high thermal conductivity.
[0240] Thus far, the manufacturing method of a joining body in which the joining material is attached to the first face of the first member and a joining portion is formed from the joining material (manufacturing method (1)) has been described, but the manufacturing method of the present embodiment can also be a manufacturing method of a joining body in which the joining material is attached to the second face of the second member and a joining portion is formed from the joining material (in the present specification, sometimes referred to as "manufacturing method (2)").
[0241] ◎ Manufacturing method (2)
[0242] Figures 3A-3E is a cross-sectional view for schematically illustrating another example of the manufacturing method of a joining body of the present embodiment, that is, the manufacturing method (2).
[0243] 《Attachment process》
[0244] In the attachment process of the manufacturing method (2), as shown in Figure 3A the joining material 130 is attached to the second face 12a of the second member 12.
[0245] In the attachment process in the manufacturing method (2), the object to which the joining material 130 is attached is not the first face 11a of the first member 11, but the second face 12a of the second member 12, and otherwise, it can be performed by the same method as in the case of the attachment process in the manufacturing method (1).
[0246]
[0247] In the drying step after the attaching step of the manufacturing method (2), as shown in Figure 3B the dried bonding material 130' is formed by drying the attached bonding material 130.
[0248] In the drying step of the manufacturing method (2), the second member 12 to which the bonding material 130 is attached is used instead of the first member 11 to which the bonding material 130 is attached, and the same method as in the case of the drying step of the manufacturing method (1) is performed except for this.
[0249] The dried bonding material 130' formed by the manufacturing method (2) is bonded to the second member 12 and is not bonded to the first member 11, and is the same as the dried bonding material 130' formed by the manufacturing method (1) except for this.
[0250] In the manufacturing method (2), since the dried bonding material 130' uses the bonding material 130, even in the case where the thickness thereof is as thick as 100 μm or more, it is possible to suppress the breakage thereof.
[0251]
[0252] In the lamination step after the drying step of the manufacturing method (2), as shown in Figure 3C the first member 11 and the second member 12 are laminated via the dried bonding material 130' to manufacture the laminate 102. That is, the laminate 102 is configured by laminating the first member 11, the dried bonding material 130', and the second member 12 in the thickness direction thereof in this order, and the dried bonding material 130' is bonded to the second member 12.
[0253] In the laminate 102, the dried bonding material 130' is bonded to the second member 12 and not to the first member 11, and is the same as the laminate 101 except for this.
[0254] In the lamination step of the manufacturing method (2), the second member 12 provided with the dried bonding material 130' is used instead of the first member 11 provided with the dried bonding material 130', and the first member 11 not provided with the dried bonding material 130' is used instead of the second member 12 not provided with the dried bonding material 130', and the same method as in the case of the lamination step of the manufacturing method (1) is performed except for this.
[0255]
[0256] In the firing step after the lamination step of the manufacturing method (2), as shown in Figure 3D As shown, the dried bonding material 130' in the laminate 102 is subjected to firing at a temperature higher than the temperature at which the bonding material 130 is dried.
[0257] The firing process in the manufacturing method (2) can be performed by the same method as in the case of the firing process in the manufacturing method (1). In the firing process in the manufacturing method (2), it is also preferable to perform pressure firing on the dried bonding material 130'.
[0258] By performing the firing process of the manufacturing method (2), as Figure 3E As shown, the bonding portion 13 is formed from the dried bonding material 130', and the target bonding body 1 is obtained. The bonding portion 13 is a metal sintered body formed from the bonding material 130 through the dried bonding material 130'. The bonding body 1 obtained by the manufacturing method (2) is the same as the bonding body 1 obtained by the manufacturing method (1).
[0259] In the case of the manufacturing method (2), by using the bonding material 130, the voids in the bonding portion 13 are also small. Therefore, even if the temperature of the bonding body 1 greatly fluctuates, the concentration of thermal stress in the bonding portion 13 is suppressed, and thus the breakage of the bonding portion 13 is suppressed. In addition, since it is formed from metal particles having high thermal conductivity, the thermal conductivity of the bonding portion 13 is high.
[0260] Example
[0261] Hereinafter, the present application will be described in more detail by specific examples. However, the present application is not limited to the examples shown below.
[0262] Note that the metal particles (A) and the metal particles (B) used in the examples or comparative examples below are each silver particles manufactured by a reduction method.
[0263] [Example 1]
[0264] Manufacture of Bonding Material
[0265] At normal temperature, the metal particles (A)-1 (silver particles of substantially spherical shape) (87 parts by mass) and Texanol (13 parts by mass) having the metal species, shape, particle size distribution, and specific surface area as shown in Table 1 were weighed on a marver, and kneaded for 15 minutes.
[0266] Next, the obtained kneaded material was passed through a three-roll mill three times, and a target paste-like bonding material was obtained.
[0267] Image data of the metal particles (A)-1 at a magnification of 10,000 times obtained using an SEM (scanning electron microscope) is as shown in Figure 4
[0268] Manufacture of Bonding Body
[0269] Formation of dried bonding material and evaluation of its cracking suppression effect
[0270] A silver-plated copper plate having a size of 20 mm x 20 mm, a thickness of 1 mm, and a silver plating layer having a thickness of 5 μm on a surface thereof was prepared.
[0271] A metal mask having a thickness of 300 μm was arranged on the surface of the silver-plated copper plate on which the silver plating layer was provided. A shape of a quadrangle having a size of 7 mm x 7 mm was printed using the bonding material. Thus, the bonding material in the shape of a quadrangle was attached to the surface of the silver-plated copper plate (attachment step).
[0272] Next, the silver-plated copper plate on which the bonding material was attached was heated at 145°C for 15 minutes using a hot air oven to dry the bonding material by volatilizing Texanol therein, and a film-shaped dried bonding material in the shape of a quadrangle was formed (drying step).
[0273] Next, the dried bonding material was visually observed, and the cracking suppression effect of the dried bonding material was evaluated in accordance with the following criteria. The results are shown in Table 1.
[0274] [Evaluation Criteria]
[0275] A: The dried bonding material did not crack at all, and the cracking suppression effect was high.
[0276] B: The dried bonding material cracked a little, and the silver-plated copper plate was not visible through the cracks, but the cracking suppression effect was poor.
[0277] C: The dried bonding material cracked significantly, and the silver-plated copper plate was visible through the cracks, and no cracking suppression effect was confirmed or the cracking suppression effect was low.
[0278] <Manufacture of Bonding Body>
[0279] A back-surface film-formed silicon carbide (SiC) chip having a size of 5 mm x 5 mm and a thickness of 0.35 mm, and having a titanium film having a thickness of 50 nm and a silver film having a thickness of 100 nm sequentially layered on one face (in other words, a back surface) by sputtering treatment was prepared.
[0280] A laminated body in which the silver-plated copper plate, the dried bonding material, and the back-surface film-formed silicon carbide chip were sequentially layered in the thickness direction thereof was produced by making the entire exposed surface of the silver film in the back-surface film-formed silicon carbide chip coincide with the face (in other words, the exposed surface) on the side opposite to the silver-plated copper plate of the dried bonding material formed as described above (lamination step).
[0281] Further, a carbon sheet ("PERMA-FOIL (registered trademark) " manufactured by Toyo Tanso Co., Ltd.) is arranged as a buffer material on the surface of the silicon carbide chip in the back surface film-formed silicon carbide chip among the laminated body.
[0282] Next, the laminated body with the carbon sheet obtained above is pressed in the thickness direction using a servo press, and the dried bonding material is pressed starting at a pressure of 15 MPa, and heating is started at a temperature increase rate of about 50°C / min.
[0283] At this time, the laminated body with the carbon sheet is arranged between a pair of press plates in the servo press. The pair of press plates has a first press plate arranged on the back surface film-formed silicon carbide chip side among the laminated body with the carbon sheet, and a second press plate arranged on the silver-plated copper plate side. The first press plate is fixed to the servo press. Then, by moving the second press plate to the first press plate side, the laminated body with the carbon sheet is supported by the first press plate, and pressure is applied to the laminated body with the carbon sheet from the silver-plated copper plate side. That is, the pressing of the laminated body with the carbon sheet at this time is performed from the silver-plated copper plate side.
[0284] Then, after the heating temperature (in other words, the temperature of the laminated body) reaches 250°C, the temperature is maintained for 5 minutes. That is, heating and pressing are performed at a temperature of 250°C and a pressure of 15 MPa for 5 minutes. In this way, by pressure sintering the dried bonding material, a bonding portion is formed from the dried bonding material (sintering process).
[0285] Next, cooling is started by flowing cooling water inside the servo press, and the pressing is released when the temperature of the laminated body reaches 60°C.
[0286] By the above, the target bonded body is obtained. The thickness of the bonding portion in the bonded body is greater than 100 μm.
[0287] "Evaluation of Bonded Body"
[0288] "Evaluation of Inhibition Effect of Generation of Void in Bonding Portion"
[0289] By mechanically polishing the side surface of the bonded body obtained above, a cross section of the bonded body is formed, and the polishing marks are removed by flat milling treatment.
[0290] Next, using SEM, 3 fields of view of a region near the center in the width direction of the joint in the cross section were randomly observed under the conditions of an acceleration voltage of 4 kV and a magnification of 5000 times. The image data thus obtained was subjected to 2-value processing using an image processing software (Image J.), and the black regions were classified as voids, and the void ratio of the joint was calculated. Then, the void generation suppression effect in the joint was evaluated in accordance with the following criteria. The results are shown in Table 1 together with the void ratio.
[0291] [evaluation criteria]
[0292] A: The average of the void ratios of the 3 fields of view was 5% or less, and the void generation suppression effect was high.
[0293] B: The average of the void ratios of the 3 fields of view was greater than 5% and 10% or less, and the void generation suppression effect was deteriorated.
[0294] C: The average of the void ratios of the 3 fields of view was greater than 10%, and no void generation suppression effect was confirmed or the void generation suppression effect was significantly reduced.
[0295] Manufacture of the bonding material, manufacture of the bonded body, evaluation of the bonded body
[0296] [Example 2]
[0297] As shown in Table 1, a bonding material was manufactured by the same method as in the case of Example 1, except that metal particles (A)-2 (approximately spherical silver particles) (87 parts by mass) were used instead of metal particles (A)-1 (87 parts by mass), and a bonded body was manufactured and evaluated. The results are shown in Table 1. The thickness of the joint in the bonded body was greater than 100 μm.
[0298] Figure 5 Image data of metal particles (A)-2 at a magnification of 10000 times obtained using SEM is shown.
[0299] [Example 3]
[0300] As shown in Table 1, a bonding material was manufactured by the same method as in the case of Example 1, except that metal particles (A)-3 (approximately spherical silver particles) (87 parts by mass) were used instead of metal particles (A)-1 (87 parts by mass), and a bonded body was manufactured and evaluated. The results are shown in Table 1. The thickness of the joint in the bonded body was greater than 100 μm.
[0301] [Comparative Example 1]
[0302] An adhesive material was produced by the same method as in the case of Example 1, except that metal particles (B)-1 (approximately spherical silver particles) (87 parts by mass) were used instead of metal particles (A)-1 (87 parts by mass), and an adhesive body was produced and evaluated. The results are shown in Table 1. The thickness of the joint portion in the adhesive body was greater than 100 μm.
[0303] Figure 6 Image data of metal particles (B)-1 at a magnification of 10,000 times, acquired using an SEM, is shown.
[0304] [Comparative Example 2]
[0305] An adhesive material was produced by the same method as in the case of Example 1, except that metal particles (B)-2 (approximately spherical silver particles) (87 parts by mass) were used instead of metal particles (A)-1 (87 parts by mass), and an adhesive body was produced and evaluated. The results are shown in Table 2. The thickness of the joint portion in the adhesive body was greater than 100 μm.
[0306] Figure 7 Image data of metal particles (B)-2 at a magnification of 10,000 times, acquired using an SEM, is shown.
[0307] [Comparative Example 3]
[0308] An adhesive material was produced by the same method as in the case of Example 1, except that metal particles (B)-3 (approximately spherical silver particles) (87 parts by mass) were used instead of metal particles (A)-1 (87 parts by mass), and an attempt was made to produce and evaluate an adhesive body. The results are shown in Table 2.
[0309] Figure 8 Image data of metal particles (B)-3 at a magnification of 10,000 times, acquired using an SEM, is shown.
[0310] [Comparative Example 4]
[0311] An adhesive material was produced by the same method as in the case of Example 1, except that metal particles (B)-4 ("N300" manufactured by Tokusen Kogyo Co., Ltd., silver particles in plate form) (87 parts by mass) were used instead of metal particles (A)-1 (87 parts by mass), and an attempt was made to produce and evaluate an adhesive body. The results are shown in Table 2.
[0312]
[0313]
[0314] From the above results, in Examples 1 to 3, even if the thickness of the dried joining material was thick, the breaking thereof was able to be suppressed. Further, even if the dried joining material was subjected to pressing at a low pressure of 15 MPa and firing, a joining portion with few voids was able to be formed. In Examples 1 to 3, the void ratio of the joining portion was 3.2% or less (2.6 to 3.2%).
[0315] In Examples 1 to 3, the joining material contained only the metal particles (A) as the metal particles, the D50 of the metal particles (A) was 0.32 to 0.48 μm, the Dmin of the metal particles (A) was 0.11 μm or more (0.11 to 0.19 μm), and the joining material did not contain a resin component.
[0316] Note that, in Examples 1 to 3, the D90 of the metal particles (A) was 0.75 μm or less (0.52 to 0.75 μm), the D10 of the metal particles (A) was 0.21 μm or more (0.21 to 0.32 μm), and the specific surface area of the metal particles (A) was 0.95 to 1.5 m 2 / g, and it was thus presumed that the joining material had more preferable properties.
[0317] On the other hand, in Comparative Example 1, the breaking of the dried joining material could not be suppressed. In Comparative Example 1, the joining material contained the metal particles (B) and did not contain the metal particles (A). The Dmin of the metal particles (B) was 0.08 μm.
[0318] In Comparative Example 2, the joining portion had many voids, and the void ratio was 6.6%. In Comparative Example 2, the joining material contained the metal particles (B) and did not contain the metal particles (A). The Dmin of the metal particles (B) was 0.08 μm, and further, the D90 of the metal particles (B) was 0.82 μm, which was large.
[0319] In Comparative Example 3, the breaking of the dried joining material was remarkable, and the silver-plated copper plate was visible through the breaking, and a joining body could not be manufactured. In Comparative Example 3, the joining material contained the metal particles (B) and did not contain the metal particles (A). The D50 of the metal particles (B) was 0.20 μm, which was too small, and the Dmin of the metal particles (B) was 0.06 μm, which was too small.
[0320] In Comparative Example 4, similarly to the case of Comparative Example 3, the breaking of the dried joining material was remarkable, and the silver-plated copper plate was visible through the breaking, and a joining body could not be manufactured. In Comparative Example 4, the joining material contained the metal particles (B) and did not contain the metal particles (A). The shape of the metal particles (B) was a plate shape.
[0321] Industrial applicability
[0322] The present application can be used for the production of an electrically conductive joint body, particularly a semiconductor device.
[0323] Explanation of symbols
[0324] 1… joint body,
[0325] 11… first member, 11a… first surface,
[0326] 12… second member, 12a… second surface,
[0327] 13… joint portion, 130… joint material, 130’… joint material after drying, 101, 102… laminate.
Claims
1. A bonding material for bonding conductive components together, comprising: Metal particles containing approximately spherical metal particles (A), and The solvent that disperses the metal particles. The particle size D50 of the metal particles (A) at 50% volume, as determined by laser diffraction / scattering particle size distribution measurement, is 0.3 to 0.5 μm, and the minimum particle size Dmin of the metal particles (A) is greater than 0.08 μm.
2. The bonding material according to claim 1, wherein, The metal particle has a metal particle (B) that is different from the metal particle (A). The minimum particle size Dmin of the metal particles (B), as determined by laser diffraction / scattering particle size distribution measurement, is greater than 0.08 μm.
3. The bonding material according to claim 1 or 2, wherein, The solvent also contains a resin component that can be a curable resin, a non-curable resin, or a thermoplastic resin. In the bonding material, the content of the resin component relative to the content of the metal particles is less than 0.01 by mass.
4. The bonding material according to claim 1 or 2, wherein, The bonding material does not contain resin components in the solvent that are curable resins, non-curable resins, or thermoplastic resins.
5. The bonding material according to claim 1 or 2, wherein, The particle size D90 of the metal particles (A) at 90% volume basis, as determined by laser diffraction / scattering particle size distribution measurement, is less than 0.8 μm.
6. The bonding material according to claim 2, wherein, Both the metal particle (A) and the metal particle (B) are silver particles.
7. The bonding material according to claim 1 or 2, wherein, The specific surface area of the metal particles (A) is between 0.95 and 1.5 m². 2 Within the range of / g.
8. A method for manufacturing a joint, comprising joining a conductive first component and a conductive second component via a conductive joint portion, wherein: The process of attaching the bonding material as described in claim 1 or 2 to the first surface of the first component or the second surface of the second component; The process of forming a dried bonding material by drying the attached bonding material; The process of laminating the first component and the second component using the dried bonding material to create a laminate; and The process of forming the joint from the dried bonding material by firing the dried bonding material in the laminate at a temperature higher than the temperature at which the bonding material is dried.
9. The method for manufacturing the joint according to claim 8, wherein, The thickness of the joint is 100 μm or more.
Citation Information
Patent Citations
Antifreeze water tap post
JP2023071339A